P440 First results of the BELCOMID study: BELgian Cohort study of COVID-19 in Immune Mediated Inflammatory Diseases (IMID). (27th May 2021) - Geldof, J; Truyens, M; Sabino, J; Ferrante, M; Lambert, J; Lapeere, H; Hillary, T; Van Laethem, A; De Vlam, K; Verschueren, P; Lobaton, T; Vermeire, S
Abstract: Background: It has been suggested that 100% of SARS-CoV2 infections leads to development of specific IgG antibodies that remain detectable for a long period of time. Targeted Immune-Modulating Therapies (TIMT) such as anti-TNF, anti-interleukins and Janus Kinase inhibitors (JAKi) for treatment of Immune Mediated Inflammatory diseases (IMID) could theoretically interfere with cytokine storm and humoral immune response against COVID19. We investigate the seroprevalence of SARS-CoV2 IgG in relation to previous exposure to COVID19 and ongoing IMID treatment in a Belgian, real-life population of IMID patients. Methods: A cross-disciplinary, prospective, observational cohort study was set up at two university hospitals. Between 17/12/2020 and 29/02/2021, all patients with IMIDs of the gut (Crohn's disease (CD), ulcerative colitis (UC)), joints (rheumatoid arthritis, psoriatic arthritis, spondyloarthritis) and skin (psoriasis, hidradenitis suppurativa, atopic dermatitis) visiting the respective clinics were asked to participate. Both patients under conventional treatment and/or TIMT were included. Patients were asked to fill out an electronic survey (REDCap®, based on WHO-ISARIC) and blood samples were drawn for serology testing (SARS-CoV-2 IgG Abbott – Architect kit®). Statistical analyses were performed with SPSS26. Results: In total 2166 IMID patients consented to take part. Of these, 1913 responded to the survey, including 218 dermatology patients, 415 rheumatology patients and 1217 IBD patients (64.7% CD, 34.3% UC, 1% undifferentiated colitis). There were 372 patients (19.5%) who reported having experienced symptoms suggestive of COVID19 (Fig. 1 ). Fatigue (61.3%), headache (48.1%), throat ache (46.9%) and dry cough (38.7%) were most frequent. Gastrointestinal symptoms such as diarrhoea or abdominal pain were present in less than 20.0% (Fig. 2 ). Ninety-six IMID patients (5.04%) had a positive SARS-CoV2 PCR test on nasal or throat swab. In 44/96 (45.8%) anti-SARS-CoV2 IgG seroconversion was confirmed. There was no significant difference in seroconversion rate between patients treated with TIMT compared to conventional therapy (P=0.192). Of the seroconverted group, 75.0% were treated with TIMT. The interval between reported positive PCR date and serology test date ranged from 3 to 24 weeks with a mean of 10 weeks. Of all survey responders, 25 were hospitalized for respiratory symptoms since 01/02/2020, six of these had positive SARS-CoV2 PCR. Conclusion: Prevalence of COVID19 symptoms and number of confirmed COVID19 cases by PCR in this cohort of IMID patients remain low regardless of treatment modality. There was no significant difference in SARS-CoV2 IgG seroconversion rate between TIMT or conventional treatment in patients with positive PCR.